(untitled) (Journal of Patan Academy of Health Sciences, 2018)
Introductions: Transmission of healthcare associated infections through contaminated hands of healthcare workers are common. This study was designed to explore the existing compliance of hand hygiene among the healthcare workers workings in different level of health care centers of Makwanpur district of Nepal. Methods: This was a cross sectional observational study conducted in Makwanpur district, Nepal, during 2015. Healthcare workers from nine healthcare centers were selected randomly for the study. Standard observation checklists and World Health Organization guidelines on hand hygiene were used to assess the compliance of hand hygiene during patient care. Results: There were 74 participants. Overall compliance for hand washing was 24.25% (range 19.63 to 45.56). Complete steps of hand washing were performed by 38.3% of health care workers. The factors associated for noncompliance were lack of time (29.3%), example set by seniors (20%), absence or inadequate institution protocol (20%) and unfavourable health care setting (> 20%). Conclusions: Overall hand washing compliance rate amongst the healthcare workers in rural health facilities of Nepal were low (24.25%).